The Implementation of Compensation for Unlawful Acts Based on Article 98 of the Code of Criminal Procedure from a Civil Law Perspective - Ulfanora Ulfanora; Almaududi Almaududi (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Indemnity is a civil case, but damages can be pursued simultaneously with criminal cases when criminal law is applied. Although criminal law laws allow claims to incorporate damages in criminal cases, this type of case is rarely found in court as not all criminal cases can be sought for damages. This situation arises when the basis of the charges in a criminal case is an act committed by the accused. The study primarily utilizes a normative juridical approach, which entails studying existing problems based on applicable laws and regulations. In legal matters related to compensation, civil law is the governing jurisdiction. On the other hand, criminal matters are regulated by the Criminal Procedure Code. In cases involving both civil and criminal actions, the judge has the power to decide whether the compensation case should be merged with the criminal case. Based on the description provided, the paper will discuss the application of Article 98 of the Code of Criminal Procedure in compensating for unlawful acts under Article 1365 of the Civil Code. The paper will also explore the legal certainty of applying Article 98 of the Code of Criminal Procedure in compensating for unlawful acts under Article 1365 of the Civil Code.